Analysis of the dominant factor of hypercholesterolemia at 45-59 years old elderly in working area of Puskesmas Rangkapanjaya Kota Depok 2016 - Widya Asih Lestari; Diah Mulyawati Utari (Berita Kedokteran Masyarakat (BKM), 2017)
Background: Hypercholesterolemia is a condition characterized by very high levels of cholesterol in the body (>200 mg/dl). Hypercholesterolemia becomes the main priority health concern in the developed and developing countries. In the late 20 years, atherosclerosis  as the cause of coronary heart shows a very significant epidemic,  in Indonesia itself, this desease ranked in 7th (5.5%). This study is aimed at analyzing the dominant factor of hypercholesterolemia at 45-59 years old pre elderly in the working area of Puskesmas Rangkapanjaya Kota Depok. Method: This study also using cross sectional design. The sample in this study is taken from 160 elderlies aged 45-49 years old in Rangkapanjaya. The data collection uses Accutrend GC, BoneScan QUS, questionnaire, food recall, and FFQ.  The data collecting techniques used in this study are chi-square and logistic regression. Result: The result of this research shows 66,25% of hypercholesterolemia proportion. The factor influencing hypercholesterolemia are vegetable intake frequency (P-value = 0,014), body mass index (P-value = 0,02), physical activity (P- value = 0,012) and bone mass  density (P-value = 0,018). It shows that the dominant factor toward hypercholesterlemia is bone mass density with OR 3,033 means man and woman with low total bone mass density has 3,033 times risk of getting hypercholesterolemia.Conclusion: Women and men with low bone density are at greater risk of developing hypercholesterolemia.